Re-embracing orality in digital education: the pedagogical affordances of podcasting in the era of generative AI - Lee, Yu-Ling; Lui, Nina Pak (Frontiers in Education, 2024)
In the evolving landscape of teacher education, where generative AI poses both opportunities and challenges, this article investigates the resurgence of orality through podcasting as a pedagogical tool. Situated within a teacher education program, the study focuses on teacher candidates who are navigating the complexities of educational technologies. It examines the role of student created podcasts for enhancing learning experiences, fostering collaborative communities, and developing essential teaching skills. Drawing on Walter Ong's theory of orality and literacy, this phenomenological research explores how a digital return to orality can effectively counterbalance the impersonal nature of AI-generated content in education. The study argues that podcasting embodies human craftsmanship, revitalizes oral traditions in learning, and equips future educators with innovative pedagogical strategies in an increasingly digital academic environment.